Optimization of a tuned vibration absorber in a multibody system by operational analysis. (September 2016) - Infante, F; Perfetto, S; Mayer, D; Herold, S
Abstract: Mechanical vibration in a drive-train can affect the operation of the system and must be kept below structural thresholds. For this reason tuned vibration absorbers (TVA) are usually employed. They are optimally designed for a single degree of freedom system using the Den Hartog technique. On the other hand, vibrations can be used to produce electrical energy exploitable locally avoiding the issues to transfer it from stationary devices to rating parts. Thus, the design of an integrated device for energy harvesting and vibration reduction is proposed to be employed in the drive-train. By investigation of the dynamic torque in the system under real operation, the accuracy of a numerical model for the multibody is evaluated. In this study, this model is initially used for the definition of the TVA. An energetic procedure is applied in order to reduce the multibody in an equivalent single degree of freedom system for a particular natural mode. Hence, the design parameters of the absorber are obtained. Furthermore, the introduction of the TVA in the model is considered to evaluate the vibration reduction. Finally, an evaluation of the power generated by the piezo transducer and its feedback on the dynamic of the drive-train is performed.